Comparative Study on Organizational Culture and Employee Commitment In India: Exploring the Link between Organizational Culture, Employee Commitment, and Performance Measurement (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Performancemanagement has been the subject of academic study for 25 years (Eccles, 1991;Johnson & Kaplan, 1987; Kaplan & Norton, 1992; Lynch & Cross, 1991;Thorpe, 2004). Neely (1999) estimated that 3,615 articles on performancemeasurement were published between 1994 and 1996 in the United States alone. Amore recent study carried out at Cranfield University also highlighted theinterest in this subject of inquiry (Franco & Bourne, 2003). Recentresearch efforts have identified leadership involvement and employeecollaboration as facilitators of increased productivity (Busi & Bititci,2006; Collins & Schmenner, 2007; Stansfield & Longenecker, 2006). As aresult of the aforementioned research, some researchers argued that performancemeasurements provide an effective way to increase the competitiveness andprofitability of the organization within the manufacturing environment